The three main steps of the Marrakech High Atlas building in Morocco: Structural evidences from the southern foreland, Imini area. (September 2015) - Leprêtre, Rémi; Missenard, Yves; Saint-Bezar, Bertrand; Barbarand, Jocelyn; Delpech, Guillaume; Yans, Johan; Dekoninck, Augustin; Saddiqi, Omar
Highlights: Three-step deformation chronology for the High Atlas building during the Cenozoic. Early(?)–Middle Miocene deformation is intrinsic to Morocco. Gravity gliding in Early(?)–Middle Miocene is linked to an early thermal uplift. Abstract: The timing of Cenozoic deformation in the intraplate orogen of the High Atlas of Morocco is still a matter of debate. In this work, the deformation calendar has been studied in the southern foreland of the Marrakech High Atlas. Using a structural approach and the mapping of the Cenomanian–Turonian reference layer, we propose a coherent chronology of deformation that proceeded in three stages: (i) a Late Eocene event that set local and minor structures, barely visible nowadays, but important enough to trigger the record of a first detrital pulse; (ii) an Early(?)–Middle Miocene event that is not related to important shortening, setting gravity "sheets" that provoke cover deformation and feed a second detrital pulse; (iii) a Late Pliocene–Quaternary event that is mainly observed through the activity of basement features like the South Atlas Front of the Imini Fault in our studied area and reworks earlier structures. This calendar can partially fit to the geodynamic changes occurring in the western Mediterranean realm during the Cenozoic. Specifically, the Early(?)–Middle Miocene stage of deformation is suggested to be intrinsic to Morocco.